'Having-to-be-thus': On Bonhoeffer's Reading of Goethe's Iphegenia in Tauris. (30th July 2018) - Phillips, Jacob
Abstract: While the intellectual background to Dietrich Bonhoeffer's Ethics is undoubtedly theological and philosophical ethical discourse, this article argues that the interpretation of an important element of the Ethics manuscripts is well-served by being approached through aesthetics, specifically poetics. The element in question is what Bonhoeffer considers a sense of 'objective necessity' involved in acting obediently to Christ, and the case that this is best approached through aesthetics is made by exploring Bonhoeffer's use of Goethe's Iphegenia in Tauris to articulate this 'objective necessity'. Working from Bonhoeffer's use of Goethe, the article explores how poetics can involve a sense of necessity comparable to that which drives the undertaking of certain ethical deeds. This possibility is found in the poetics of the philosopher Wilhelm Dilthey, who considers this poetic and ethical necessity always to be concrete, and coins a category for it, named 'having-to-be-thus'. Examining this category promises to contribute to the difficult theological question of how concrete obedience to Christ can be 'objectively necessary' at all, but also point more broadly to the aesthetic character of Bonhoeffer's ethical stipulations.